The Promising Impact of Ibrutinib, a Bruton's Tyrosine Kinase Inhibitor, for the Management of Lymphoid Malignancies. Issue 3 (12th December 2013) - Bhatt, Valkal; Alejandro, Linh; Michael, Angela; Ganetsky, Alex
<x xml:space="preserve">Abstract</x> Lymphoid malignancies comprise a heterogeneous group of disorders originating from clonal proliferation of B or T lymphocytes. Treatment of lymphoid neoplasms has traditionally been pursued with cytotoxic chemotherapy. To improve efficacy and ameliorate the adverse effects associated with classic chemotherapy, molecularly targeted therapy has been developed. At the forefront of clinical development is ibrutinib, an inhibitor of Bruton's tyrosine kinase (Btk). Btk is a protein tyrosine kinase that plays an important role in regulating B‐cell signaling. Dysregulated Btk results in uncontrolled B‐lymphocyte proliferation, differentiation, and survival. Ibrutinib is currently being studied in numerous malignancies of lymphoid origin including chronic lymphocytic leukemia, mantle cell lymphoma, non‐Hodgkin lymphoma, follicular lymphoma, and multiple myeloma. Thus far, ibrutinib has demonstrated very promising results in treatment‐naive patients as well as those with relapsed or refractory disease with an acceptable safety profile. In this article, we describe the pharmacology, efficacy, and toxicity profile of ibrutinib and depict the potential role that ibrutinib will play in the treatment paradigm of lymphoid neoplasms.